Writing beyond the call: One woman's response to Gloria Anzaldúa's "Speaking in Tongues". Issue 2 (June 2017) - Rideaux, Kia S
In her manuscript, "Speaking in Tongues: A Letter to Third World Women Writers, " author Gloria Evangelina Anzaldúa composes several open and honest letters to women of color, challenging them to actively incorporate the process of writing into their everyday lives. She encourages her readers to engage in organic writing by recapturing their own silenced narratives. In response, the following letters reflect on the lasting impact of Anzaldúa's words and how we might incorporate her ideals of literary activism into our own writing practices. Particularly, the following text will consider how those drawn to epistemologies of the Global South might resist mechanisms of sameness and in doing so begin to rethink how we situate our own stories within the realm of early childhood.